GREEN ECONOMICS: PAVING THE PATH TO SUSTAINABLE GROWTH AND ENVIRONMENTAL STEWARDSHIP - K. Punitha; G. Rameshkumar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Green economics represents a transformative approach to economic theory and practice, one that prioritizes sustainability, environmental stewardship, and equitable growth. As the world grapples with the dual challenges of environmental degradation and economic inequality, green economics offers a viable framework to reconcile economic development with ecological limits. This paper explores the core principles of green economics, evaluates its potential for fostering sustainable growth, and examines the role of governments, businesses, and individuals in implementing green policies. Through a comparative analysis of case studies from various regions, the paper highlights the success stories and challenges faced by green economic initiatives. Finally, it outlines policy recommendations aimed at achieving sustainable economic systems that prioritize the environment and human well-being.